The Influence of Independence and Mathematical Communication Skills on Student Learning Outcomes in the Material of Relations and Functions - Amrullah; Sulisyani, Anis; Kurniati, Nani (Balai Publikasi Indonesia, 2024)
The independent and communication skills in mathematics learning are two very important competency components that students must master and greatly influence student learning outcomes. However, students at SMPN 4 Mataram have relatively low independence and mathematical communication skills. As a result, student learning outcomes obtained by more than 50% are classically below the KKM. Therefore, this research focuses on two variables that influence learning outcomes, namely independence and mathematical communication skills. This research uses quantitative methods. The population was 125 class VIII students. Using Simple Random Sampling, a sample of 32 students was obtained. Data on class VIII students at SMPN 4 Mataram for the 2023/2024 academic year was collected using questionnaires and tests. By using regression analysis the results obtained were 1) There was an influence of independence on student learning outcomes in relation and function material of 25,4%; 2) There is an influence of mathematical communication skills on learning outcomes V of 43,8%. 3) There is an influence of independence and mathematical communication skills together on student learning outcomes in relation and function material of 72,4%